Perancangan Sistem Kontrol Kecepatan Kapal dengan Sistem Propulsi Hibrida Berbasis Fuzzy-PID - Afifah, Rahma Nuruf; Kurniawan, Edi; Ajie, Kuntoro Bayu; Santoso, Agus Dwi; Rakhman, Rizqi Aini (Jurnal Ilmiah Global Education, 2026)
This study aims to design and determine the Fuzzy-PID control system for ship speed with a hybrid propulsion system. This system is designed to increase the efficiency of fuel use in Internal Combustion Engines, so it is expected to reduce exhaust emissions in the environment. The control system uses Fuzzy-PID control which aims to determine the effectiveness of using the Fuzzy-PID method on ships with hybrid propulsion systems. The design of this system involves the use of a pixhawk as a ship speed monitor, an STM32 microcontroller as a data processor, an ICE engine as a main engine, a BLDC motor as an auxiliary propulsion engine, a photodiode sensor as an RPM reader on the main engine and BLDC motor, and the Fuzzy-PID method as an error value processing. The results of the experiments conducted, experiments without control produced the largest error value compared to experiments with control, with an average error value of 30.4%, experiments with PID control produced an average error value of 30.2% and experiments with Fuzzy PID control optimization produced the smallest average error value of 22.4%. The lowest fuel consumption was found in the PID-controlled experiment, with the lowest consumption at 6.44 mL during the experiment with a setpoint speed of 4.87 knots.